ANALYSIS OF THE FILM-FORMING CAPACITY OF POLYMER DISPERSIONS FOR THE CREATION OF HYBRID COATINGS - PLAVAN, VIKTORIIA; KOLODIY, ARTEM; OKHMAT, OLENA (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The article is devoted to the analysis of polymer dispersions from different types to determine the possibility of their further use as part of hybrid polymer coatings for functionalizing of the fibrous materials surface. PLEXTOL UF PR 3500K (Synthomer, Great Britain) is an aqueous dispersion of an acrylic copolymer with an ultra-fine particle size. CRILAT 4815 (Vinavil, Italy) is an aqueous acrylic dispersion. Impranil® DLP-R (Covestro, Germany) is an anionic aliphatic polyester-polyurethane dispersion suitable for use in textile coatings for outerwear, luggage and technical products. VINAVIL EVA 4612 (Vinavil, Italy) is an aqueous dispersion of a copolymer of vinyl acetate and ethylene. The quality of water-emulsion polymer dispersions and the possibility of their use in the process of the fibrous materials surface functionalization was determined by their film-forming ability, resistance to water and organic solvents, mechanical characteristics (film tensile strength, relative elongation at break), film stickiness and other properties. Almost all polymer films demonstrate resistance to elevated temperatures. Films from acrylic dispersions demonstrate solubility in most organic solvents, except for ethylene glycol, in contrast to films from polyurethane dispersions, which exhibit high resistance to all organic solvents. Polyurethane films demonstrate the highest degree of swelling in butyl acetate (23.8%). All films demonstrate the ability to swell in water, the highest degree of swelling of 61.73% is for the acrylic film with Crilat 4815, the lowest degree of swelling is for the polyurethane film (1.33%). It was determined that to obtain a sufficiently elastic, non-sticky polymer coating with high mechanical strength, while maintaining a low degree of swelling of the films in water, it is advisable to use dispersions of acrylic copolymer Plextol VF 3500 or Crilat 4815 and polyester-polyurethane dispersion Impranil DLP-R. Further research will be aimed at choosing a rational ratio of the mentioned film formers and developing technological parameters of finishing.